Computing at school: Teaching Scratch Programming - Alexandrini, Fábio (2023)
The insertion of adolescents in technological knowledge has been increasingly necessary, not only because of the pandemic, but because we live in a globalized world where basic computer knowledge is essential. In view of this need, students in the 8th and 9th years of the State Schools of Basic Education Henrique Da Silva Fontes, Willi Hering and Luís Ledra in Rio do Sul were taught. Through the Computação nas Escolas project, which uses the basic programming platform Scratch, to create animations and fun games that seek to generate interest, for those who know how to train new professionals in the digital areas, which is a market that is currently on the rise. In classes, films with themes that cover the social aspect behind technology are also used in order to generate debates on the subject. All of this resulted in a positive result, because with this project it ended up generating the first contact of many students with such technologies, and many created an interest in possibly pursuing a career in the area of Information Technology, five of them, by the way, are studying the Computer Technician for Internet at the Federal Institute Catarinense(IFC) and possibly in the future the Graduation of Computer Science. In addition to these, there are reports of other students studying at institutions such as the National Service for Industrial Learning (SENAI) and the National Service for Commercial Learning (SENAC), which also offer this technical course.